Efficacy and safety of oral beclomethasone dipropionate and budesonide MMX 5-aminosalicylates or placebo in ulcerative colitis: a systematic review and meta-analysis - Brigida Barberio; Ilaria Marsilio; Andrea Buda; Luisa Bertin; Gianluca Semprucci; Annalisa Zanini; Martina Crepaldi; Fabiana Zingone; Edoardo Savarino (Therapeutic Advances in Gastroenterology, 2023)
Background: Low bioavailability steroids, including beclomethasone dipropionate (BDP) and budesonide MMX, have been developed to ensure colonic targeting and low systemic activity than systematic corticosteroids in treating patients with ulcerative colitis (UC). Objectives: This systematic review and meta-analysis evaluated the efficacy and safety of BDP and budesonide MMX® compared with 5-aminosalicylic acid (5-ASAs) or placebo, in patients with mild-to-moderate UC. Design: Systematic review and meta-analysis Methods: We searched MEDLINE, EMBASE, and the Cochrane central register of controlled trials from inception to December 2021. We included all available randomized controlled trials (RCTs) comparing oral BDP or budesonide MMX with 5-ASAs or with placebo in induction of remission of mild-to-moderate UC. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Results: We identified two RCTs comparing BDP 5 mg with 5-ASA, one RCTs comparing BDP 10 mg with 5-ASA, two RCTs BDP 5 mg versus placebo, one RCT BDP 10 mg versus placebo, two RCTs budesonide MMX 9 mg versus 5-ASA, and six RCTs budesonide MMX 9 mg versus placebo. In terms of achieving clinical remission or improvement, BDP 5 mg, BDP 10 mg, and budesonide MMX 9 mg were more effective than placebo (OR 2.36, 95% CI 1.37–4.08; OR 2.23, 95% CI 1.02–4.87; and OR 2.03, 95% CI 1.45–2.85, respectively). The drugs were also more effective than placebo in achieving endoscopic remission. Regarding the comparisons with 5-ASA, we found no differences between 5-ASA and BDP 5 mg or BDP 10 mg or budesonide MMX 9 mg in achieving clinical remission or improvement (OR 0.90, 95% CI 0.51–1.57; OR 1.54, 95% CI 0.42–5.64; and OR 1.17, 95% CI 0.82–1.66). However, 5-ASA was more effective than budesonide MMX 9 mg in achieving histological remission (OR 0.33, 95% CI 0.16–0.70). Overall, all the drugs were safe and well tolerated. Conclusion: Low bioavailability steroids were more effective than placebo in achieving clinical remission, clinical and endoscopic remission, and histological remission. No differences were found between 5-ASA and BDP or budesonide MMX. Surely, more RCTs, also comparing BDP and budesonide MMX, are mandatory to confirm or not these results.